2010
DOI: 10.1186/1476-0711-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Spondylodiscitis and an aortic aneurysm due to Campylobacter coli

Abstract: Campylobacter coli is a rare cause of bacteremia. We report here the first case of C.coli spondylodiscitis complicated by an aortic aneurysm. Outcome was favourable with surgery and antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Campylobacter bacteremia has been found to have an incidence of 0.1% to 1% in relation to enteritis (5), and patients aged 65 or higher had an incidence which was 3 times higher than that in younger age groups (10). In line with other reports about Campylobacter spondylodiscitis, our patient was over 60 years of age (1,3,6,12,13) and had an underlying medical condition (8,12). However, cases without explicit predisposing conditions have also been reported in the elderly (3,6,13), and Campylobacter bacteremia studies showed inconsistent results regarding patient age and underlying diseases (5).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Campylobacter bacteremia has been found to have an incidence of 0.1% to 1% in relation to enteritis (5), and patients aged 65 or higher had an incidence which was 3 times higher than that in younger age groups (10). In line with other reports about Campylobacter spondylodiscitis, our patient was over 60 years of age (1,3,6,12,13) and had an underlying medical condition (8,12). However, cases without explicit predisposing conditions have also been reported in the elderly (3,6,13), and Campylobacter bacteremia studies showed inconsistent results regarding patient age and underlying diseases (5).…”
supporting
confidence: 79%
“…As also seen in our case, spondylodiscitis due to Campylobacter spp. is often accompanied by nearby abscesses, such as in the psoas muscle (3,6), near the vertebral column (1,6), or near the dura mater (12,13). One case of concomitant pyogenic meningoencephalitis has also been described (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found 2 severe complications during or immediately after bacteremic episodes, Guillain-Barré syndrome and cervical spondylodiscitis in 1 patient each. Although C. coli has been reported to cause spondylodiscitis [ 35 ], to the best of our knowledge, this is the first time a patient with C. jejuni bacteremia is reported to have spondylodiscitis. The bacterial aspirate, obtained during surgical drainage of the spinal abscesses, was negative, probably owing to the already initiated appropriate antimicrobial treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This allows the immediate AST-/MIC-adapted EUCASTrecommended antibiotic treatment in immunocompromised febrile patients suffering from Campylobacter-induced haemorrhagic diarrhoea. It remains unclear whether this reported Campylobacter sepsis case was related to previous dasatinib therapy, underlying CML disease or a highly virulent Campylobacter strain (Wu et al, 2013;Lemaire et al, 2010). Further clinical studies are warranted in this respect.…”
Section: Discussionmentioning
confidence: 93%